Retrieving Organs, Losing Motivation? The Response of Medical Staff to Corruption News - Maximilian Mähr; Alida Sangrigoli; Giuseppe Sorrenti; Gilberto Turati (CESifo GmbH, 2024)
This paper examines how media coverage of corruption scandals influences the behavior of public healthcare workers, specifically ICU medical staff involved in organ procurement. Using Italy's National Health Service as a case study, we investigate the behavioral responses of medical staff to two corruption scandals—one involving a hospital manager and the other a surgeon. By employing a difference-in-differences strategy across regions with varied exposure to media coverage, we isolate the impact of corruption-related news on reported organ donors. Our findings indicate that media coverage of the surgeon scandal, but not the manager scandal, significantly reduces reported donors, likely due to heightened sensitivity among staff to corruption within their professional ranks. Additional text analysis reveals no substantial semantic differences in reporting between the two scandals, suggesting that the observed effects stem from the shared professional mission among ICU staff rather than from media bias. The results underscore the indirect costs of corruption on public sector performance, with potential negative welfare implications for organ donation rates.
Keywords: D64; D73; H41; I18; 330; corruption; worker motivation; organ procurement